Evaluation of The Social Care Program of Regional Leadership Council Partai Amanat Nasional (PAN) of Batu City in Spraying Disinfectants - Utomo, Imam Wahyu; Larasati, Puteri Nur Anisa; Wahyu, Fernandha; Vinedal, Alung (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
This study aims to produce an Evaluation of Care Program in spraying Disinfectant to Prevent the Spread of Corona Virus by the Regional Leadership Council (DPD) Partai Amanat Nasional (PAN) of the Batu City. The method used in this study is a qualitative research method. Data collection techniques by observation, interview and documentation. The model used is non participatory evaluation research. The results of this study are programs run by the Regional Representative Council (DPD) of the partai Amanat Nasional (PAN) of Batu City in the form of a social care program for spraying disinfectants to prevent the spread of the corona virus through inanimate objects in the Batu City area. because of their initial goal of doing this program for the hurricane and foundations in the Batu City area, when residents heard that spraying was being done by the Regional Representative Council (DPD) of Partai Amanat Nasional (PAN) of Batu City, enthusiastic attitudes of the community immediately arose to ask for spraying in the village they were so Regional Representative Council (DPD) Partai amanat Nasional (PAN) of Batu city experienced constraints in the volunteer workforce.